Promoting equity in adolescent health in Latin America: designing a comprehensive Sex education program using Intervention Mapping. A mixed methods study - Torres-Cortés, Betzabé; Leiva, Loreto; Canenguez, Katia M.; Greaves, Lorraine (Frontiers in Reproductive Health, 2024)
IntroductionImplementing sex education programs during adolescence is crucial for addressing the risks associated with sexuality. However, some of these interventions lack proper incorporation of a gender perspective and maintain a heteronormative and biologically-focused approach, potentially resulting in inequitable outcomes for adolescents. In response, comprehensive sex education is most effective due to its multidimensional view of sexuality. However, integrating a comprehensive perspective on sexuality and a gender lens that contributes to adolescent health equity presents challenges, especially in low and middle-income countries. This study aimed to develop a comprehensive and gender-transformative sex education program for adolescents in a middle-income country of Latin America, utilizing the Intervention Mapping Approach.MethodsThis exploratory sequential mixed-method study comprised two phases. In the first phase, a literature review, nine focus groups with high school students, and 14 interviews with school professionals were conducted to inform program design. Subsequently, the program underwent validation through expert judgment. In the second phase—as part of program development—a preliminary evaluation was conducted by implementing the program in two high schools with 30 students from public high schools, who were administered a pre-post ad hoc survey.ResultsA comprehensive and gender-transformative sex education program was designed based on literature review findings and input from students and school workers. The ad hoc survey revealed a statistically significant increase in protective skills in sexuality (W = 59, p = .01) among all participants.DiscussionDesigning a sex education intervention through Intervention Mapping allowed for the integration of evidence and the needs of the target population. The results of the preliminary evaluation suggest the potential of the developed program to enhance protective skills in sexuality and promote health equity through gender-equitable outcomes in adolescent sex education.